P-684 The impact of oral sphingosine-1-phosphate analogue on ovarian aging in women with multiple sclerosis. (30th June 2022) - Kender Ertürk, N; Erturk, A; Karakoc Sokmensuer, L; Yarali, H; Bozdag, G; Mumusoglu, S
Abstract: Study question: Is there a protective effect of oral sphingosine-1-phosphate analogue (S1P) on ovarian reserve? Summary answer: The use of oral long acting S1P analogue may reduce spontaneous primordial follicle loss and preserve ovarian reserve in women of reproductive age. What is known already: The number of primordial follicles decrease by apoptosis with advancing age in women. Seramid pathway is one of the apoptosis regulatory pathways in human ovaries. An increase in the balance between ceramide and S1P in S1P direction, known as cell membrane sphingomyelins, inhibits follicular apoptosis. Fingolimod (Novartis, Germany), a long-acting oral analogue of S1P, is a drug used in the treatment of multiple sclerosis (MS). We have previously found that use of fingolimod might reduce the spontaneous follicular apoptosis and increase the number of residual primordial follicles in a rat model. Study design, size, duration: A prospective cohort study. Twenty-one consecutive women in reproductive age to whom fingolimod therapy were commenced for MS at Hacettepe University, Department of Neurology in between 2018 – 2021were included. Participants/materials, setting, methods: Regularly menstruating women under <38 years old was included. Serum Anti-Mullerian Hormone (AMH) levels were measured at the beginning of Fingolimod, 6th and 12th months of the treatment. The decrease in serum AMH levels were calculated and compared with standard AMH decrease in healthy women. Main results and the role of chance: The mean±standard deviation (SD) age of the 21 patients was 26.95±6.07. The mean±SD of AMH level at the beginning was 2, 62±1, 64 ng/ml. The respective figure for the 6th month and 12th month were 3, 10±2, 02 and 1, 70±1, 70 ng/ml. Overall, there was an increase of 0.6 ng/ml in mean AMH during this period. AMH level decreased in 2 patients, remained unchanged in 2 patients, and increased in 5 patients. Limitations, reasons for caution: High (∼50%) loss to follow-up rate is a main limitation. Wider implications of the findings: Oral long-acting MS drug fingolimod may have a protective effect on ovarian reserve in human by reducing spontaneous follicle loss rate, studies with larger sample size and longer follow-up period is warranted to demonstrate this effect. Trial registration number: not applicable